Korotkoff sounds dynamically reflect changes in cardiac function based on deep learning methods - Lin, Wenting; Jia, Sixiang; Chen, Yiwen; Shi, Hanning; Zhao, Jianqiang; Li, Zhe; Wu, Yiteng; Jiang, Hangpan; Zhang, Qi; Wang, Wei; Chen, Yayu; Feng, Chao; et al. (Frontiers in Cardiovascular Medicine, 2022)
Korotkoff sounds (K-sounds) have been around for over 100 years and are considered the gold standard for blood pressure (BP) measurement. K-sounds are also unique for the diagnosis and treatment of cardiovascular diseases; however, their efficacy is limited. The incidences of heart failure (HF) are increasing, which necessitate the development of a rapid and convenient pre-hospital screening method. In this review, we propose a deep learning (DL) method and the possibility of using K-methods to predict cardiac function changes for the detection of cardiac dysfunctions.